An approach to achieve IT agility by combining SOA with ITSM. (1st October 2010) - Izza, Said; Imache, Rabah
Today, service-orientation is considered as a compelling technique for developing agile software systems that best align with business. It is also considered as an important approach for information technology (IT) service management, especially for service delivery and support. However, there is still some confusions and misunderstanding between people as sometimes they are referring to information technology service management (ITSM) services and sometimes to service-oriented architecture (SOA) services. So, the combination of both SOA and ITSM approaches arises. This paper deals with this combination and it provides some principles, policies and models that guide and explain the connections that may exist between the two worlds. Specifically, it provides a service model and governance, which cover the multitude necessary activities for specifying and managing how services are defined and supported within large enterprises.